In vivo assessment of Lactobacillus plantarum strains in black tiger shrimp (Penaeus monodon): implications for growth performance, probiotic-pathogen interaction, and defense against AHPND infection - Chin, Yong Kit; Wan Omar, Haifa-Haryani; Nazarudin, Muhammad Farhan; Ahmad, Mohd Ihsanuddin; Azzam-Sayuti, Mohamad; Mohd Ali, Nur Shidda; Ngalimat, Mohamad Syazwan; Mohamad, Aslah; Ida-Muryany, Md Yasin; Karim, Murni; Salleh, Annas; Mohd Nor, Norhariani; et al. (Springer, 2024)
Acute hepatopancreatic necrosis disease (AHPND) is an emerging disease that has recently severely damaged global shrimp aquaculture industries. Aside from antibiotics, using a probiotic, Lactobacillus spp., can become an alternative for AHPND prevention in shrimp aquaculture. Therefore, this study aims to screen the most suitable Lactobacillus strains for black tiger shrimp (Penaeus monodon) against AHPND. Forty-nine lactic acid bacteria were identified out of 232 isolates from fresh wild-caught fish and shrimp in the local wet market. From there, six Lactobacillus spp. strains were chosen for the hemolytic test, colony top assay, well diffusion assay, and co-culture assay. Subsequently, three strains of L. plantarum, including strains L20, KD2, and T31, were chosen for feeding trial. Bacterial dosages of 108 CFU/mL of the L. plantarum were incorporated into basal feed, respectively. A total of 600 shrimp postlarvae (PL15) were distributed into 4 treatment groups (control, L20, KD2, and T31) with triplicates. Shrimp in treatment groups were fed with different supplemented feeds for 35 days. On the 35th day, all shrimp were challenged via immersion with 6 × 105 CFU/mL of Vibrio parahaemolyticus S2-4 positive AHPND. All shrimp from the feeding trial and the challenge test were sampled for gene expression and histopathology throughout the study. Results revealed that L. plantarum strain L20 was the best probiotic among the three strains since it improved shrimp growth performance during the feeding trial, shrimp gastrointestinal microbiota, and survival of P. monodon postlarvae against V. parahaemolyticus S2-4 in the challenge test. This study demonstrated the potential allochthonous L. plantarum L20 as a probiotic in shrimp against AHPND, which causes significant losses in the aquaculture industry of Malaysia.